Work-Related Fatigue Factors among Hospital Nurses: An Integrative Literature Review - Alahmadi, Bader Abdullah; Alharbi, Manal Fehade (Department of Nursing, Faculty of Medicine, Diponegoro University, 2018)
Background: Due to the demanding nature of nurses’ work and the current shortage of nurses, hospital nurses often find themselves working extra shifts, extended hours, and taking on more responsibilities. However, this added pressure on the body and mind results in fatigue which adversely affects nurses' health status as well as their ability to provide optimal health care procedures. Preventing fatigue and reducing its adverse consequences require comprehensive awareness about its diverse contributing factors.Purpose: This study aimed to examine factors which influence fatigue among nurses employed in a hospital setting.Methods: An integrative review was conducted to assess the quality of the research evidence, to find minor and major gaps in current research and the main issues in the area of the research and finally to bridge the research gaps. This integrative review identified a total of 12 relevant research studies from Cumulative Index to Nursing and Allied Health Literature (CINAHL), Medline, Embase, PsycINFO, and a manual search. Data were reviewed in May 2017, using an integrative review, and then interpreted, analyzed and synthesized to identify the key contributing factors that influence fatigue among hospital nurses.Results: The review revealed that significant factors such as organizational factors, nursing work characteristics, psychosocial factors as well as individual characteristics and demand, influenced the nurse fatigue. Work shifts, specifically night shifts and extended work shifts without sufficient inter-shift recovery were linked to higher levels of fatigue.Conclusion: This review identified the significant factors affecting fatigue among nurses in hospital settings in various countries all around the world. Findings from this study may help healthcare organizations and policymaker to introduce strategies that mitigate fatigue among nurses.